STRENGTHENING THE LAW IN ORDER TO KEEP EXISTENCE THE UNITARY STATE OF THE REPUBLIC OF INDONESIA - Rokhmat Bowo Suharto (International Journal of Law Reconstruction, 2020)
The Unitary State of the Republic of Indonesia (NKRI) was founded on the support of diversity, both ethnicity, religion, and customs. As historical, the building of such a nation could not be separated from the various tests, beginning of rebellions based on ethnicity, religion, and political ideology, to replace the form of a union state with the enactment of the Constitution. RIS has also occurred. In fact, the Republic of Indonesia remained standing up to this moment. As a law that addresses the entire existing local legal system, the Indonesian legal system has actually placed various means integration which is at the same time the national identity of the Republic of Indonesia building. Associated with the goal of the existence of the Republic of Indonesia, the existing legal construction needs to be strengthened by conducting a paradigmatic evaluation that is continuous and continuous related to (1) legal pluralism policy; (2) legalistic legal paradigm; (3) Central and Regional Relations and local communities; (4) Cultivation of cultural aspects and social capital in development policies; (5) the division of public and private space related to the expression of differences between various cultural, religious or ethnic communities; and (6) Liberalization of political life.